Adaptation of the professionalism mini-evaluation exercise instrument into Turkish: a validity and reliability study - AKDENİZ, ESRA; GÜLPINAR, MEHMET ALİ (My University, 2023)
Background: There is an ongoing search for standardized scales appropriate for each culture to evaluate professionalism, which is one of the basic competencies of a physician. The Professionalism Mini-evaluation Exercise (P-MEX) instrument was originally developed in Canada to meet this need. In this study, it was aimed to adapt the P-MEX to Turkish and to evaluate the validity and reliability of the Turkish version. Methods: A total of 58 residents at Bakirkoy Dr. Sadi Konuk Training and Research Hospital were assessed with the Turkish version of P-MEX by 24 raters consisting of faculty members, attending physicians, peer residents, and nurses during patient room visits, outpatient clinic and group practices. For construct validity, the confirmatory factor analysis was performed. For reliability, Cronbach’s alpha scores were calculated. Generalizibility and decision studies were undertaken to predict the reliability of the validated tool under different conditions. After the administration of P-MEX was completed, the participants were asked to provide feedback on the acceptability, feasibility, and educational impact of the instrument. Results: A total of 696 forms were obtained from the administration of P-MEX. The content validity of P-MEX was found to be appropriate by the faculty members. In the confirmatory factor analysis of the original structure of the 24-item Turkish scale, the goodness-of-fit parameters were calculated as follows: CFI = 0.675, TLI = 0.604, and RMSEA = 0.089. In the second stage, the factors on which the items loaded were changed without removing any item, and the model was modified. For the modified model, the CFI, TLI, and RMSEA values were calculated as 0.857, 0.834, and 0.057, respectively. The decision study on the results obtained from the use of P-MEX in a Turkish population revealed the necessity to perform this evaluation 18 times to correctly evaluate professionalism with this instrument. Cronbach’s alpha score was 0.844. All the faculty members provided positive feedback on the acceptability, feasibility, and educational impact of the adapted P-MEX. Conclusion: The findings of this study showed that the Turkish version of P-MEX had sufficient validity and reliability in assessing professionalism among residents. Similarly, the acceptability and feasibility of the instrument were found to be high, and it had a positive impact on education. Trial registration: 2020/249, Bakirkoy Dr. Sadi Konuk Training and Research Hospital.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Educational measurement; Medical professionalism; Residency